Two-step secant type method with approximation of the inverse operator - Shakhno, S.M.; Yarmola, H.P. (Carpathian Mathematical Publications, 2013)
The two-step secant type method with a consistent approximation of the inverse operator for solving nonlinear equations is proposed. The local convergence of the proposed method is studied and the quadratic convergence order is established. A numerical experiment is made on the test problems.